Novel engineered TRAIL‐based chimeric protein strongly inhibits tumor growth and bypasses TRAIL resistance. Issue 4 (24th January 2020) - Rozga, Piotr; Kloska, Damian; Pawlak, Sebastian; Teska‐Kaminska, Malgorzata; Galazka, Marlena; Bukato, Katarzyna; Pieczykolan, Anna; Jaworski, Albert; Molga‐Kaczmarska, Anna; Kopacz, Aleksandra; Badyra, Bogna; Kachamakova‐Trojanowska, Neli; et al.
Abstract : Targeting of the TRAIL‐DR4/5 pathway was proposed as a promising approach for specific induction of apoptosis in cancer cells. Clinical trials, however, showed inadequate efficiency of TRAIL as a monotherapy. It is a widely held view that the application of multifunctional molecules or combination therapy may lead to substantial improvement. Here, we demonstrate the effectiveness and safety of a novel chimeric protein, AD‐O51.4, which is a TRAIL equipped with positively charged VEGFA‐derived effector peptides. The study was performed in multiple cancer cell line‐ and patient‐derived xenografts. A pharmacokinetic profile was established in monkeys. AD‐O51.4 strongly inhibits tumor growth, even leading to complete long‐term tumor remission. Neither mice nor monkeys treated with AD‐O51.4 demonstrate symptoms of drug toxicity. AD‐O51.4 exhibits a satisfactory half‐life in plasma and accumulates preferentially in tumors. The cellular mechanism of AD‐O51.4 activity involves both cytotoxic effects in tumor cells and antiangiogenic effects on the endothelium. The presence of DRs in cancer cells is crucial for AD‐O51.4‐driven apoptosis execution. The TRAIL component of the fusion molecule serves as an apoptosis inducer and a cellular anchor for the effector peptides in TRAIL‐sensitive and TRAIL‐resistant cancer cells, respectively. The FADD‐dependent pathway, however, seems to be not indispensable in death signal transduction; thus, AD‐O51.4 is capable of bypassing the refractoriness of TRAIL. AD‐O51.4‐driven cell death, which exceeds TRAIL activity, is achieved due to the N‐terminally fused polypeptide, containing VEGFA‐derived effector peptides. The high anticancer efficiency of AD‐O51.4 combined with its safety has led to the entry of AD‐O51.4 into toxicological studies. Abstract : What's new? Targeting death receptors like those bound by tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) is an attractive alternative to cytotoxic chemotherapy but death receptor agonists, applied as single agents, are therapeutically ineffective. The authors developed a fusion protein, AD‐O51.4, combining TRAIL with positively charged peptides derived from vascular endothelial growth factor A, the major mediator of angiogenesis. AD‐O51.4 exerted both cytotoxic and antiangiogenic effects in various cancer models while bypassing resistance to TRAIL‐induced cell death, encouraging a similar approach with other death receptor ligands.